Chromium plating layer manufacturing method and plating apparatus

JP7637392B2Active Publication Date: 2025-02-28KAMIYA RIKEN CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022137147
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-08-30
Publication Date
2025-02-28
Estimated Expiration
2042-08-30

AI Technical Summary

Benefits of technology

【0009】 本発明の一態様によれば、鉛又は鉛合金電極を使用せず、鉛又は鉛合金と同程度の酸化効率を有するアノード電極を用いたクロムめっき層の製造方法が提供される。 また、本発明の別の態様によれば、金属クロムめっきに用いる、鉛又は鉛合金電極を使用しないめっき装置が提供される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007637392000001
    Figure 0007637392000001
  • Figure 0007637392000002
    Figure 0007637392000002
  • Figure 0007637392000003
    Figure 0007637392000003
Patent Text Reader

Abstract

To provide a production method of a chromium plating layer using an anode electrode having oxidation efficiency almost the same as that of a lead or a lead alloy electrode without using a lead or a lead alloy electrode, and a plating apparatus which is used for a chromium plating without using a lead or a lead alloy electrode.SOLUTION: A plating apparatus comprises: a plating tank in which an electrolyte including hexavalent chromium ions and a sulfuric acid is reserved; an anode including a conductive diamond, at least a part of which contacts the electrolyte; a cathode which is a to-be-plated object; and an external power source for connecting the anode and the cathode. Using the plating apparatus, a production method of a chromium plating layer includes steps of: applying voltage to the electrolyte using the anode including the conductive diamond; reducing the hexavalent chromium ions included in the electrolyte by electrolysis; and forming the chromium plating layer on the cathode.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for producing a chrome plating layer and a plating apparatus. [Background technology]

[0002] Chrome plating has been used as a method for electrolytically depositing metal films with excellent wear resistance, corrosion resistance, and appearance on the surface of industrial products. In the chrome plating process, hexavalent chromium ions are reduced on the cathode, and metallic chromium is electrolytically deposited via trivalent chromium ions. However, some trivalent chromium ions are not reduced to metallic chromium and are released from the cathode into the electrolyte, increasing the concentration of trivalent chromium ions in the electrolyte. The increase in the concentration of trivalent chromium ions causes a decrease in the covering power of chrome plating. Therefore, it is necessary to convert the trivalent chromium ions in the electrolyte back to hexavalent chromium ions by anodic oxidation, and to suppress the increase in the concentration of trivalent chromium ions. Since the oxidation-reduction potential from trivalent chromium ions to hexavalent chromium ions is higher than the oxygen evolution potential of water, an anode with a high oxygen overvoltage is required for the anodic oxidation of trivalent chromium ions. Conventionally, a lead electrode or a lead alloy electrode with a high oxygen overvoltage has been used as the anode electrode in order to improve the efficiency of anodic oxidation.

[0003] However, lead, including lead contained in lead alloys, has problems such as the reaction with chromate ions contained in the electrolyte, causing deterioration of the anode electrode over time, and the reaction producing insoluble lead chromate, which accumulates at the bottom of the plating tank. For example, as a method for suppressing deterioration over time of an anode electrode using lead or a lead alloy, a technology has been disclosed in which weight loss of the lead or lead alloy electrode is suppressed by using an electrolyte to which a chromium source, an alkylsulfonic acid having a specific structure, bismuth, arsenic or antimony ion source has been added (see Patent Document 1). In addition, to address the issues of increasing the maximum current density while keeping the voltage low, making the anode current density uniform, and suppressing the curvature of the anode, a chrome plating anode with an anode structure has been proposed in which a hollow cylindrical lead alloy is prepared and a copper core is inserted into the hollow part of the lead alloy and pressure-welded (see Patent Document 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] U.S. Pat. No. 4,786,378 [Patent Document 2] JP 2001-158999 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, both Patent Document 1 and Patent Document 2 disclose technologies premised on the use of lead or a lead alloy for the anode electrode, and for example, Patent Document 1 suppresses the deterioration of the electrode using lead over time, but does not prevent the deterioration itself, and does not improve the need to remove the lead chromate that accumulates at the bottom of the plating tank, and the removed lead chromate becomes lead-containing waste, which incurs high costs for its disposal. Furthermore, there is a possibility that workers may come into contact with lead during the process of removing the lead chromate, and improvements are also desired from the viewpoint of the working environment. The use of platinum, which has a lower environmental impact and does not use lead, as the anode electrode has been considered, but its low oxidation efficiency makes it difficult to use it as a replacement for lead.

[0006] An object of the present invention is to provide a method for producing a chromium plating layer using an anode electrode having an oxidation efficiency comparable to that of lead or a lead alloy without using a lead or lead alloy electrode.An object of the present invention is to provide a plating apparatus for use in metal chromium plating without using a lead or lead alloy electrode. [Means for solving the problem]

[0007] Means for solving the above problems include the following embodiments.

[0008] [1] A method for producing a chrome plating layer includes a step of using a plating apparatus equipped with a plating tank in which an electrolyte containing hexavalent chromium ions and sulfuric acid is stored, an anode containing conductive diamond at least partially in contact with the electrolyte, a cathode which is an object to be plated, and an external power supply which connects the anode and the cathode, applying a voltage to the electrolyte from the external power supply to reduce the hexavalent chromium ions contained in the electrolyte by electrolysis, and forming a chrome plating layer on the cathode. [2] The method for producing a chrome plating layer according to [1], wherein the conductive diamond in the anode is conductive diamond doped with 1.0 atom % to 2.0 atom % of boron. [3] The method for producing a chrome plating layer according to [1] or [2], wherein the hexavalent chromium ions contained in the electrolytic solution include at least one selected from the group consisting of chromate ions, dichromate ions, and trichromate ions, each of which has chromium trioxide as an ion raw material. [4] The method for producing a chromium plating layer according to [3], wherein the content of chromium trioxide in the electrolytic solution is 200 g / L to 300 g / L, and the content of sulfuric acid in the electrolytic solution is 2.0 g / L to 3.0 g / L. [5] A plating apparatus comprising: a plating tank; an electrolyte stored in the plating tank; an anode including a conductive diamond, at least a portion of which is in contact with the electrolyte; and a cathode, which is an object to be plated. [6] The plating apparatus according to [5], further comprising an external power source for applying a voltage to the anode, a device for adjusting the temperature of the electrolytic solution, and a filter for filtering the electrolytic solution. [7] The plating apparatus according to [5] or [6], wherein the conductive diamond in the anode is conductive diamond doped with 1.0 atom % to 2.0 atom % of boron. [8] The plating apparatus according to any one of [5] to [7], wherein the electrolytic solution contains at least one type of hexavalent chromium selected from the group consisting of chromate ions, dichromate ions, and trichromate ions, with chromium trioxide as an ion raw material. [9] The plating apparatus according to any one of [5] to [8], wherein the content of chromium trioxide in the electrolytic solution is 200 g / L to 300 g / L, and the content of sulfuric acid in the electrolytic solution is 2.0 g / L to 3.0 g / L. Effect of the Invention

[0009] According to one aspect of the present invention, there is provided a method for producing a chromium plating layer using an anode electrode having an oxidation efficiency comparable to that of lead or a lead alloy without using a lead or lead alloy electrode. According to another aspect of the present invention, there is provided a plating apparatus for use in metal chromium plating that does not use lead or lead alloy electrodes. [Brief description of the drawings]

[0010] [Figure 1] 1 is a schematic diagram showing an example of a plating apparatus according to the present disclosure. [Diagram 2] 1 is a graph showing a change in the concentration of trivalent chromium ions in an electrolytic solution when electrolysis is performed in the electrolytic solution by changing the type of anode in a plating apparatus. [Diagram 3] 1 is a graph showing a change in concentration of trivalent chromium ions in an anode electrolyte when electrolysis is performed in the electrolyte using various anodes in a state in which the anode electrolyte and the cathode electrolyte are separated by an ion exchange membrane. [Figure 4]FIG. 4(A) shows a digital microscope image of the surface of the chrome plating layer electrodeposited on the cathode when the plating apparatus applied in Example 1, which used a conductive diamond electrode as the anode, was used, and FIG. 4(B) shows a digital microscope image of the surface of the chrome plating layer electrodeposited on the cathode when the plating apparatus applied in Comparative Example 1, which used a lead alloy electrode as the anode, was used. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the method for producing a chrome plating layer according to the present disclosure using the plating apparatus according to the present disclosure will be described with reference to the drawings. Note that the present disclosure is not limited to the embodiments described below, and includes various modified examples that do not depart from the gist of the present disclosure.

[0012] <Method of manufacturing chrome plating layer> The method for producing a chrome plating layer of the present disclosure (hereinafter, sometimes referred to as the "method of the present disclosure") includes the steps of using a plating apparatus equipped with a plating tank in which an electrolyte containing hexavalent chromium ions and sulfuric acid is stored, an anode containing conductive diamond at least partially in contact with the electrolyte, a cathode which is the object to be plated, and an external power supply connecting the anode and the cathode, applying a voltage to the electrolyte from the external power supply, reducing the hexavalent chromium ions contained in the electrolyte by electrolysis, and forming a chrome plating layer on the cathode.

[0013] The function of the method disclosed herein is not clear, but the electrode containing conductive diamond has high oxygen overvoltage and is chemically stable, so that the electrode containing conductive diamond is used as the anode to form a chrome plating layer, and the trivalent chromium ion in the electrolyte is oxidized to hexavalent chromium ion on the anode containing conductive diamond, even without using lead or lead alloy electrode.As a result, it is presumed that the increase in the concentration of trivalent chromium ion in the electrolyte can be suppressed, and the reduction in the covering power of the chrome plating layer formed on the cathode surface can be suppressed. In addition, according to the present invention, by using a conductive diamond electrode as an anode, it is possible to suppress the increase in the concentration of trivalent chromium ions in the electrolyte. In addition, it is possible to eliminate the generation of lead-containing waste such as lead chromate. Furthermore, it is possible to improve the working environment by eliminating contact between workers and lead. In addition, according to the present invention, a chrome plating apparatus that does not require the removal of lead chromate is provided.

[0014] The electrolyte used in the method of the present disclosure contains hexavalent chromium ions. The hexavalent chromium ions contained in the electrolytic solution preferably include at least one selected from the group consisting of chromate ions, dichromate ions, and trichromate ions. Chromium trioxide can be used as a raw material for the at least one ion selected from the group consisting of chromate ions, dichromate ions, and trichromate ions. When the electrolytic solution contains chromium trioxide, which is an ion raw material, the chromium trioxide dissolves in the electrolytic solution to generate ions, and the electrolytic solution contains at least one ion selected from the group consisting of chromate ions, dichromate ions, and trichromate ions derived from chromium trioxide.

[0015] From the viewpoint of obtaining a faster plating speed, the content of chromium trioxide in the electrolytic solution used in the method of the present disclosure is preferably high, for example, 200 g / L to 300 g / L. In addition, the addition of sulfuric acid that functions as a plating catalyst is important for the electrolytic solution, and from the viewpoint of facilitating the function as a catalyst, the amount of sulfuric acid added to the electrolytic solution is preferably about 1 mass % relative to the total amount of trivalent chromium, that is, 2.0 g / L to 3.0 g / L. The content of chromium trioxide in the electrolytic solution is more preferably 230 g / L to 270 g / L. The content of chromium trioxide in the above-mentioned electrolytic solution is the charged amount, and in the electrolytic solution, chromium trioxide is in the form of hexavalent chromium ions. The content of trivalent chromium in the electrolyte can be measured by ion chromatography, ultraviolet-visible absorbance spectroscopy (UV-Vis absorbance analysis) using an ultraviolet-visible spectrophotometer, or the like. The content of sulfuric acid in the electrolytic solution is more preferably 2.3 g / L to 2.7 g / L. The content of sulfuric acid in the above-mentioned electrolytic solution is the charged amount, and the sulfuric acid in the electrolytic solution is dissociated into hydrogen ions and sulfate ions.

[0016] The electrolyte used in the method of the present disclosure may further contain known additives, in addition to hexavalent chromium ions and sulfuric acid, if desired. As the additive, fluoroalkylsulfonic acid can be added. For example, fluoromethanesulfonic acid can be mentioned. It is preferable that the electrolytic solution further contains fluoroalkylsulfonic acid, since the current efficiency of chromium plating is further improved. Here, the current efficiency means the ratio of the current consumed for the electrodeposition of chromium to the current supplied between the anode and the cathode. Incidentally, non-fluorinated alkylsulfonic acids such as methanesulfonic acid, which are known as additives to electrolytes, are oxidatively decomposed on the anode containing conductive diamond, as described below, and are therefore unsuitable as additives to electrolytes.

[0017] The anode in the method of the present disclosure uses an anode electrode containing conductive diamond. The anode electrode containing conductive diamond is composed of a conductive substrate and a conductive diamond thin film located on the surface of the conductive substrate. The anode electrode containing conductive diamond used in the method of the present disclosure has high hardness, high oxygen overvoltage, low electrolytic consumption, and excellent chemical stability. There is no particular limitation on the method for forming a conductive diamond thin film on a conductive substrate, but a gas phase method such as a vapor deposition method can be applied. The method for forming conductive diamond is described in detail below.

[0018] The anode electrode including the conductive diamond has an electrical contact with a lead wire. The lead wire has an electrical contact with at least one of the conductive diamond thin film and the conductive substrate, and may have an electrical contact with both the conductive diamond thin film and the conductive substrate.

[0019] One method for imparting electrical conductivity to the diamond thin film in the anode electrode is to dope it with boron. Specifically, for example, a boron compound such as diborane or trimethoxyborane is added to a raw material gas serving as a carbon source, and a thin film is formed by a vapor phase method, thereby obtaining a boron-doped conductive diamond thin film. The doping amount of boron in the conductive diamond can be set to 0.10 atom % to 2.0 atom % relative to the number of carbon atoms constituting the diamond, and is preferably 1.0 atom % to 2.0 atom %. That is, the conductive diamond is preferably a conductive diamond doped with 1.0 atom % to 2.0 atom % of boron. When the conductive diamond is boron-doped diamond with a doping amount of 1.0 atom % to 2.0 atom %, the conductive diamond exhibits high oxygen overvoltage and electrical conductivity, and has advantageous properties. It should be noted that "atom %" here is synonymous with "atomic number %," and the doping amount of boron atoms is a value based on the number of atoms constituting diamond.

[0020] Methods for forming a conductive diamond thin film on the anode include chemical vapor deposition (CVD), such as hot filament chemical vapor deposition (HFCVD). When producing boron-doped diamond, for example, a conductive substrate such as titanium is fixed inside a film-forming apparatus, and a film-forming raw material gas containing hydrogen as a carrier gas, methane as a carbon source, and diborane as a boron source is supplied into the film-forming apparatus. The raw material gas is decomposed by the heat of the filament, and carbon is deposited while maintaining the sp3 structure, and boron is further absorbed, resulting in boron-doped diamond. As a method for forming a conductive diamond thin film other than CVD, a physical vapor deposition method such as an ion plating method can be used. The thickness of the conductive diamond thin film is not particularly limited as long as the conductive substrate can be covered without contacting the electrolyte, but considering durability, it is preferable that the thickness is 5 μm to 20 μm. From the viewpoint of plating efficiency, the conductive diamond thin film can be thin without any problem, but from the viewpoint of durability, it is preferable that the thickness is thick, so that within the above range, both plating efficiency and durability are at a level that does not cause any practical problems. The thickness of the conductive diamond thin film can be confirmed by observing a cross section using an electron microscope.

[0021] As the conductive substrate used for the anode electrode containing conductive diamond, any known conductive substrate made of a material having electrical conductivity can be appropriately selected and used. Examples of the conductive substrate include a semiconductor substrate such as p-type silicon, and a metal substrate such as titanium or niobium. Among them, titanium and niobium are preferred from the viewpoint of further suppressing corrosion of the substrate during plating treatment.

[0022] There is no particular limit to the size and shape of the conductive diamond-containing anode electrode used in the method of the present disclosure, and they can be appropriately selected in consideration of the characteristics of the object to be plated, the thickness of the desired chrome plating layer, etc. Generally, from the viewpoint of usability, a size of 1 cm 2 ~100cm 2 The anode electrode containing the conductive diamond may be a rectangular plate having an area of ​​100 mm and a thickness of 2 mm. This is just an example, and the size of the anode electrode containing the conductive diamond may be determined depending on the size of the plating device.

[0023] In the anode containing conductive diamond, the conductive diamond thin film is entirely or partially immersed in an electrolyte, and a voltage is applied to the anode. However, it should be avoided to immerse the contact area between the anode electrode containing conductive diamond and the lead wire joined to the electrode in the electrolyte, since there is a risk of corrosion of the contact area.

[0024] In the method of the present disclosure, an object to be plated is used as the cathode. There are no limitations on the object to be plated as long as it is a material having electrical conductivity. The material of the object to be plated is not particularly limited, except that it is conductive. Examples of the material of the object to be plated include steel and nickel. The type and content of carbon and other metals contained in the steel are selected according to the purpose. Iron itself can also be used as the object to be plated. The object to be plated is fixed to a jig having electrical contacts, which are made of a material having excellent electrical conductivity such as copper or aluminum.

[0025] There are no particular limitations on the size and shape of the object to be plated as the cathode, but from the viewpoint of suppressing the generation of trivalent chromium ions on the object to be plated, it is preferable that the surface area of ​​the object to be plated be half or less of the surface area of ​​the anode electrode containing conductive diamond. This is because the smaller the surface area of ​​the object to be plated is, the less the amount of trivalent chromium ions produced on the cathode.

[0026] When forming a chrome plating layer on an object to be plated by the method of the present disclosure, it is preferable to subject the object to an appropriate pretreatment in advance according to the material of the object to be plated. For example, when steel is used as the object to be plated, the steel can be pretreated by alkaline degreasing, alkaline electrolytic degreasing, acid activation treatment, etc. For example, impurities such as oil and fat are removed from the surface of the object to be plated by the degreasing treatment, which improves the formability of the plating layer.

[0027] In the method of the present disclosure, the chrome plating layer may be produced by controlling at least one of the voltage and current density applied between the anode and the cathode by an external power source. The current may be a direct current or a pulse current.

[0028] In the method of the present disclosure, the cathode current density during the production of the chrome plating layer is 10 A / dm 2 ~30A / dm 2 It can be up to 25A / dm 2 ~30A / dm 2 It is preferable to set the above.

[0029] In the method of the present disclosure, the voltage between the anode and the cathode, which is the object to be plated, during production of the chrome plating layer can be 0.1 V to 15 V. The voltage between the anode and the cathode can be appropriately determined taking into consideration the current density, the surface area of ​​the object to be plated, the composition of the electrolyte, etc.

[0030] In the method of the present disclosure, an external power supply can be used to apply a voltage to the anode. The external power supply has a function of controlling the voltage and current. The external power supply preferably has, for example, a galvanostat function for maintaining the current during electrolysis at a certain value. The external power supply must have an output that is sufficient to supply the necessary voltage and current. As the external power supply, a known power supply may be used, such as a silicon rectifier.

[0031] In the method disclosed herein, an anode containing conductive diamond at least partially in contact with the electrolyte and a cathode, which is the object to be plated and immersed in the electrolyte, are used in a plating tank in which an electrolyte containing hexavalent chromium ions and sulfuric acid is stored, and a voltage is applied to the electrolyte using the anode from the external power source, thereby reducing the hexavalent chromium contained in the electrolyte by electrolysis, and forming a chrome plating layer on the cathode, which is the object to be plated.

[0032] The anode containing conductive diamond used in the method of the present disclosure has high oxygen overvoltage and excellent chemical stability, so that even without using lead or lead alloy electrode, it can suppress the increase in the concentration of trivalent chromium in the electrolyte, and suppress the decrease in the covering power of the chromium plating layer formed on the cathode surface.Furthermore, even after producing the chromium plating layer, it does not generate undesirable lead-containing waste such as lead chromate in the electrolyte, so it is a method that is favorable in terms of working environment and has a wide range of applications.

[0033] As a plating apparatus applicable to the method of the present disclosure, the plating apparatus of the present disclosure shown below is preferable.

[0034] <Plating equipment> The plating apparatus of the present disclosure comprises a plating tank, an electrolyte stored in the plating tank, an anode containing conductive diamond at least partially in contact with the electrolyte stored in the plating tank, and a cathode which is the object to be plated. The plating apparatus of the present disclosure preferably further comprises an external power source for applying a voltage to the anode, a device for adjusting the temperature of the electrolytic solution, and a filter for filtering the electrolytic solution.

[0035] The anode, cathode, electrolyte, and external power source used in the plating apparatus of the present disclosure are the same as those listed in the method of the present disclosure described above, and preferred examples are also the same. Specifically, the conductive diamond contained in the anode in the plating apparatus is preferably conductive diamond doped with 1.0 atom % to 2.0 atom % of boron. The electrolytic solution stored in the plating bath of the plating device preferably contains at least one type of hexavalent chromium ion selected from the group consisting of chromate ions, dichromate ions, and trichromate ions, with chromium trioxide as the ion raw material, and the content of chromium trioxide in the electrolytic solution is preferably 200 g / L to 300 g / L, and the content of sulfuric acid in the electrolytic solution is preferably 2.0 g / L to 3.0 g / L.

[0036] The plating apparatus of the present disclosure preferably includes an external power supply for applying a voltage to the anode. The external power supply has a function of controlling the voltage and current. The external power supply preferably has, for example, a galvanostat function for maintaining the current during electrolysis at a certain value. The external power supply must have an output sufficient to supply the necessary voltage and current. As the external power supply, a known power supply may be used, for example, a silicon rectifier.

[0037] The plating apparatus of the present disclosure preferably includes a temperature sensor and a heater for adjusting the temperature of the electrolytic solution stored in the plating tank. The temperature sensor is not particularly limited as long as it can accurately measure the temperature of the electrolyte. As the temperature sensor, a device that can be used by immersing the sensor part in the electrolyte can be used. As a temperature sensor that can be used in the plating device of the present disclosure, for example, a platinum resistor coated with perfluoroalkoxyalkane (PFA) can be mentioned. A heater linked to the temperature sensor operates according to the temperature of the electrolyte measured by the temperature sensor, and the temperature of the electrolyte in the plating tank can be maintained at a temperature suitable for plating. By maintaining the temperature of the electrolyte within a suitable range, the efficiency of forming the plating layer is further improved. The temperature of the electrolyte may be 45°C to 55°C. There is no particular limitation on the heater that can be used in the plating apparatus of the present disclosure, and any known heater can be used as appropriate. Examples of the heater include an electric heater covered with polytetrafluoroethylene (PTFE). Among these, the portion of the heater that comes into contact with the electrolyte is preferably made of a fluororesin such as PTFE, titanium, tantalum, quartz, or the like, from the viewpoint of stability.

[0038] The plating apparatus of the present disclosure may include a pump and a filter for filtering the electrolytic solution. When a chrome plating layer is continuously formed on the cathode surface, the electrolytic solution is collected by a pump, and after removing solid matter through a filter, the electrolytic solution is supplied to the plating tank, thereby improving the production efficiency of the chrome plating layer on the cathode. The flow rate of the pump can be appropriately determined depending on the size of the plating tank in the plating apparatus.

[0039] The plating apparatus of the present disclosure will be described with reference to FIG. 1, which shows an example of a plating apparatus. The plating apparatus 10 shown in FIG. 1 includes an anode 12, a cathode 14, a plating tank 18, an electrolytic solution 20 stored in the plating tank 18, an external power supply 16, a temperature sensor 22, a heater 24, a pump 26 that circulates the electrolytic solution stored in the plating tank, and a filter 28 that removes solid matter from the electrolytic solution. An electrode containing conductive diamond is used as the anode 12. An object to be plated is used as the cathode 14. It is preferable to stir the electrolytic solution 20 in the plating tank 18. The electrolytic solution in the plating tank can be stirred by circulating the electrolytic solution 20 stored in the plating tank 18 using a pump 26. If desired, the plating tank may be provided with a separate stirring device for stirring the electrolytic solution.

[0040] The production of a chrome plating layer using the plating bath of the present disclosure can be carried out by the following procedure. (1) Pour the electrolyte into the plating tank. The electrolyte is heated to a constant temperature using a heater while stirring the electrolyte. It is preferable to maintain the temperature of the electrolyte within a constant range using the heater while measuring the temperature of the electrolyte with a temperature sensor. (2) The electrode containing the conductive diamond is placed in a plating tank as an anode, and the anode is brought into contact with the electrolyte stored in the plating tank. (3) Preferably, a pretreated object to be plated is fixed in a plating tank as a cathode. (4) Immediately afterwards, a voltage is applied to the anode from an external power source, and plating is performed on the cathode, which is the object to be plated, to form a chrome plating layer. EXAMPLES

[0041] The method and plating apparatus of the present disclosure will be specifically described below using examples. However, the examples merely illustrate one aspect of the present disclosure, and the present disclosure is not limited to the examples shown below.

[0042] [Example 1] (Manufacture of an anode containing conductive diamond) An anode electrode containing conductive diamond was fabricated by depositing a conductive diamond film on a conductive substrate by the hot filament CVD method. The conductive substrate has a surface area of ​​50 cm 2 A titanium plate (Nilaco Corporation) with a thickness of 0.2 mm was used. The conductive diamond film was formed using a CVD device with a flow rate ratio of methane:hydrogen:boron source gas=3:200:0.01. It was then confirmed that a conductive diamond thin film had been formed on the conductive substrate. The amount of boron doped in the conductive diamond thin film formed on the conductive substrate was measured using a secondary ion mass spectrometer (CAMECA, IMS-7f) and found to be 17,000 ppm (1.7 atom %). The cross section of the conductive diamond thin film was observed using an electron microscope, and the thickness of the conductive diamond thin film was measured to be about 5 μm.

[0043] The anode electrode having the conductive diamond thin film thus prepared was masked with Teflon tape to reduce the surface area to 15 cm 2 In addition, a gold wire was used to make electrical contact with the anode electrode having a conductive diamond thin film. In order to clean the surface of the conductive diamond electrode, it was electrolytically oxidized in a 0.1 M aqueous sulfuric acid solution at a constant current of 100 mA for 15 minutes before use.

[0044] (Manufacturing of chrome plating layers) An anode electrode containing conductive diamond was fixed in the plating tank of the plating apparatus shown in FIG. Surface area 5cm 2 An iron plate was fixed in the plating tank as a cathode. An electrolyte solution was prepared containing 250 g / L of chromium trioxide and 2.5 g / L of sulfuric acid in water as a solvent. 200 ml of the obtained electrolyte solution was poured into a plating tank. The plating tank was a thermostatic tank equipped with a temperature sensor and a heater, and the temperature of the electrolyte was kept at 50°C. The electrolyte solution was continuously stirred using a magnetic stirrer. The current density at the cathode is 30A / dm 2 A constant current was supplied to the cathode using an external power source so as to perform electrolysis. The iron plate serving as the cathode was replaced with a new one every six hours, and the supply of a constant current was continued for 50 hours to carry out Evaluation 1 described below.

[0045] [Control Example 1] As a control example, a chrome plating layer was produced in the same manner as in Example 1, except that a lead alloy electrode (Pb:Sn weight ratio = 95:5, Yamamoto Plating Tester) was used instead of the anode electrode containing conductive diamond used in Example 1.

[0046] In the above Example 1 and the Control Example, the following evaluations were carried out for each of the electrolytic solutions and the formed chromium plating layers.

[0047] (Evaluation 1: Measurement of trivalent chromium ion concentration in electrolyte: Effect of suppressing increase in trivalent chromium ion concentration) To measure the concentration of trivalent chromium ions in the electrolyte, the electrolyte was sampled at regular intervals, diluted five-fold, and the absorbance of the diluted solution at 590 nm was measured using a UV-Vis spectrophotometer (Hitachi, U-2000). The results are shown in Figure 2. Figure 2 is a graph showing the change in concentration of trivalent chromium ions in an electrolytic solution when electrolysis is performed in the electrolytic solution in a plating device. As a result, the change in the concentration of trivalent chromium ions over time was obtained, as shown in Figure 2. In Example 1, which used an anode electrode containing conductive diamond, the concentration of trivalent chromium ions was kept in the range of 0.93 g / L to 1.42 g / L, and it is understood that the increase in the concentration of trivalent chromium ions over time during the plating process was suppressed. A similar tendency was observed when the lead alloy electrode, which is the control example 1, was used. When the lead alloy electrode, which is a known anode electrode, was used, the evaluation was continued for about 20 hours, and it was confirmed that the increase in the trivalent chromium ion concentration was also suppressed.

[0048] According to previous knowledge on metal chrome plating, it is known that the coverage of chrome plating, i.e., the formability of the chrome plating layer, decreases when the concentration of trivalent chromium is 7g / L or more. It was confirmed that the anode electrode containing conductive diamond used in Example 1 maintained the concentration of trivalent chromium at an appropriate level for up to 50 hours and exhibited characteristics similar to those of the lead alloy electrode that has been used conventionally for chrome plating.

[0049] (Evaluation 2: Electrolytic oxidation of trivalent chromium ions using an electrode) In the anode electrode containing conductive diamond used in Example 1, the surface area of ​​the electrode was masked to 30 cm for evaluation purposes. 2 As in Example 1, electrolytic oxidation was carried out in an aqueous sulfuric acid solution to clean the surface.

[0050] The conductive diamond-containing anode electrode in Example 1 and the lead alloy electrode in Comparative Example 1 were fixed as anodes in the same plating bath as that used in Evaluation 1. 2 A platinum electrode (Nilaco Corporation) was fixed in the plating tank. In the plating tank, the anode and cathode were separated using a cation exchange membrane (AGC, Selemion AMV), and 150 ml of electrolyte was poured into the anode side, and 50 ml of electrolyte was poured into the cathode side. The electrolyte used contained 250 g / L of chromium trioxide, 2.5 g / L of sulfuric acid, and 10 mmol / L of chromium (III) sulfate. While stirring the electrolyte using a magnetic stirrer, the cathode current density was set to 5A / dm 2 A constant current was supplied to the cathode so that the electrolysis was carried out continuously for 6 hours.

[0051] In order to measure the concentration of trivalent chromium ions in the electrolyte, the electrolyte was sampled at regular intervals. The sampled electrolyte was diluted 5 times to prepare a diluted solution, and the absorbance at 590 nm was measured using a UV-Vis spectrophotometer (Hitachi, U-2000). The results are shown in Figure 3. Figure 3 is a graph showing the change in concentration of trivalent chromium in the anolyte electrolyte when electrolysis was performed in the electrolyte using various anodes, with the anolyte electrolyte and the catholyte electrolyte separated by an ion exchange membrane.

[0052] As shown in Fig. 3, the concentration of trivalent chromium ions in the anolyte changed over time in the case of the anode electrode containing conductive diamond used in Example 1. When the anode electrode containing conductive diamond was used, the concentration of trivalent chromium ions in the anolyte decreased over time, suggesting that the trivalent chromium ions were oxidized to hexavalent chromium ions on the anode electrode. In the case of the lead alloy electrode used in Comparative Example 1, the concentration of trivalent chromium ions decreased as in Example 1. This suggests that, even in the case of using the lead alloy electrode, trivalent chromium ions were oxidized to hexavalent chromium ions on the anode electrode.

[0053] It is believed that the anode electrode containing conductive diamond in Example 1 and the lead alloy electrode in Comparative Example 1 both had high oxygen overvoltage, and therefore oxidation of trivalent chromium ions proceeded in parallel with water electrolysis.

[0054] When an anode electrode containing conductive diamond was used, the current efficiency for the oxidation reaction of trivalent chromium ions 1 hour after the start of electrolysis was 9.58%. When a lead alloy electrode was used, the current efficiency for the oxidation reaction of trivalent chromium ions 1 hour after the start of electrolysis was 8.31%. In this case, the current efficiency is the ratio of the charge consumed for the oxidation of trivalent chromium ions to the total charge contained in the supplied current. From the above results, it was confirmed that the anode electrode containing conductive diamond exhibits high activity for the oxidation reaction of trivalent chromium ions, similar to that of the conventionally known lead alloy electrode.

[0055] (Evaluation 3: Properties of the obtained chrome plating layer) After carrying out the experiment of Example 1, the physical properties of the chromium plating layer obtained on the cathode were evaluated. Elemental analysis was performed using a fluorescent X-ray coating thickness meter (BOWMAN, BA-100), hardness measurement was performed using a Vickers hardness tester (Future-Tech, FM-300e), and morphological observation was performed using a digital microscope (Keyence, VHX-2000). In Example 1, the results of the fluorescent X-ray analysis of the obtained chromium plating layer confirmed a clear chromium Kα ray peak, indicating that the chromium plating layer was a high-purity chromium layer. Moreover, the hardness of the chromium plating layer obtained in Example 1 was Hv983, which was a high hardness. The hardness of the chromium plating layer obtained in Control Example 1 was Hv991, which was a high hardness. These results show that the hardness of the chrome plating layer obtained using an anode electrode containing conductive diamond is equivalent to that of the chrome plating layer obtained using a lead alloy electrode, and that both exhibit hardness levels that are acceptable for practical use.

[0056] FIG. 4(A) is a microscope image of the chrome plating layer obtained in Example 1, and FIG. 4(B) is a microscope image of the chrome plating layer obtained in Comparative Example 1. Clear cracks were observed in both images. The cracks on the plating layer surface in the microscope images are a morphology unique to chrome plating layers. From the above physical property evaluation results, it was confirmed that the characteristics of the chrome plating layer obtained when a conductive diamond electrode was used exhibited excellent characteristics similar to those of the chrome plating layer obtained when a lead alloy electrode was used.

[0057] [Comparative Example 1] As a substitute for the lead electrode or lead alloy electrode, a known platinum electrode was used as the anode electrode. That is, except that a platinum electrode (platinum plate, Nilaco Corporation) was used as the anode electrode instead of the anode electrode containing conductive diamond, the current density at the cathode was set to 30 A / dm 2 Electrolysis was carried out by continuously supplying a constant current to the cathode using an external power source so that In the same manner as in Example 1, Evaluation 1 and Evaluation 2 were carried out.

[0058] (Rating 1) In Comparative Example 1, the concentration of trivalent chromium ions in the electrolyte was measured in the same manner as in Example 1. The results are also shown in FIG. As is clear from FIG. 2, when a platinum electrode was used as the anode in Comparative Example 1, the concentration of trivalent chromium ions increased over time, and no suppression effect on the concentration of trivalent chromium ions was observed. After about 18 hours, the concentration of trivalent chromium ions reached 7 g / L or more, at which point the formability of the chrome plating layer is thought to decrease, and the evaluation was terminated. (Rating 2) In Comparative Example 1, the change in concentration of trivalent chromium ions in the anolyte was measured when electrolysis was performed in the electrolyte in a state in which the anolyte and the catholyte were separated using an ion exchange membrane, in the same manner as in Example 1. The results are shown in Figure 3. 3, when the platinum electrode was used in Comparative Example 1, the concentration of trivalent chromium ions in the anodic electrolyte did not change, and no oxidation reaction of trivalent chromium ions was observed. This is probably because the platinum electrode has a low oxygen overvoltage, so most of the supplied current was consumed in generating oxygen through water electrolysis, and the trivalent chromium ions were not oxidized.

[0059] [Comparative Example 2] As an alternative to a lead electrode or a lead alloy electrode, a known iridium oxide was used as the anode electrode. That is, instead of an anode electrode containing conductive diamond, an iridium oxide electrode (20 g / m on a titanium substrate) was used as the anode electrode. 3 The same procedure as in Example 1 was repeated except that an electrode on which iridium oxide was deposited (JCU Corporation) was used, and the current density at the cathode was set to 30 A / dm 2 Electrolysis was carried out by continuously supplying a constant current to the cathode using an external power source so that In the same manner as in Example 1, Evaluation 1 and Evaluation 2 were carried out.

[0060] (Rating 1) In Comparative Example 2, the concentration of trivalent chromium ions in the electrolyte was measured in the same manner as in Example 1. The results are shown in FIG. As is clear from FIG. 2, when iridium oxide was used as the anode electrode in Comparative Example 2, the concentration of trivalent chromium ions increased over time, and no suppression effect on the concentration of trivalent chromium ions was observed, so the evaluation was terminated after about 18 hours. (Rating 2) In Comparative Example 2, the change in concentration of trivalent chromium ions in the anolyte was measured when electrolysis was performed in the electrolyte in a state in which the anolyte and the catholyte were separated using an ion exchange membrane, in the same manner as in Example 1. The results are shown in Figure 3. 3, when the iridium oxide electrode was used in Comparative Example 1, the concentration of trivalent chromium ions in the anodic electrolyte did not change, and no oxidation reaction of trivalent chromium ions was observed. This is thought to be because the oxygen overvoltage of the iridium oxide electrode was low, so most of the supplied current was consumed in generating oxygen through water electrolysis, and the trivalent chromium ions were not oxidized. Therefore, in Comparative Example 1 and Comparative Example 2, the concentration of trivalent chromium ions in the electrolyte was not maintained within an appropriate range. [Industrial Applicability]

[0061] According to the method for producing a chrome plating layer and the plating apparatus of the present disclosure, it is possible to produce a good chrome plating layer without using a lead electrode or a lead alloy electrode. In addition, since no lead or lead alloy is used, it is possible to produce a chrome plating layer that is favorable in terms of the working environment. [Explanation of symbols]

[0062] 10 Plating Equipment 12 Anode (anode electrode containing conductive diamond) 14 Cathode (item to be plated) 16 External power supply 18 Plating tank 20 Electrolyte 22 Temperature Sensor 24 Heater 26 Pump 28 Filters

Claims

1. A plating tank in which an electrolytic solution containing hexavalent chromium ions and sulfuric acid is stored; an anode including a conductive diamond, the anode being at least partially in contact with the electrolyte; A cathode which is an object to be plated; an external power source connecting the anode and the cathode; Using a plating apparatus equipped with A step of applying a voltage to the electrolytic solution by the external power source, reducing hexavalent chromium ions contained in the electrolytic solution by electrolysis, and forming a chromium plating layer on the cathode, A method for producing a chrome plating layer, wherein the anode is an anode having a conductive substrate not containing lead or a lead alloy and a conductive diamond thin film formed on the conductive substrate.

2. 2. The method for producing a chrome plating layer according to claim 1, wherein the conductive diamond in the anode is a conductive diamond doped with 1.0 atom % to 2.0 atom % of boron.

3. 3. The method for producing a chrome plating layer according to claim 1 or 2, wherein the hexavalent chromium ions contained in the electrolytic solution include at least one selected from the group consisting of chromate ions, dichromate ions, and trichromate ions, each of which has chromium trioxide as an ion raw material.

4. The method for producing a chromium plating layer according to claim 3, wherein the content of chromium trioxide in the electrolytic solution is 200 g / L to 300 g / L, and the content of sulfuric acid in the electrolytic solution is 2.0 g / L to 3.0 g / L.

5. The plating apparatus includes a plating tank, an electrolytic solution stored in the plating tank, an anode including a conductive diamond at least partially in contact with the electrolytic solution, and a cathode which is an object to be plated; The electrolyte contains hexavalent chromium ions and sulfuric acid, The plating apparatus, wherein the anode is an anode having a conductive substrate not containing lead or a lead alloy and a conductive diamond thin film formed on the conductive substrate.

6. 6. The plating apparatus according to claim 5, further comprising an external power source for applying a voltage to the anode, a device for adjusting the temperature of the electrolytic solution, and a filter for filtering the electrolytic solution.

7. 6. The plating apparatus according to claim 5, wherein the conductive diamond in the anode is conductive diamond doped with 1.0 atom % to 2.0 atom % of boron.

8. 6. The plating apparatus according to claim 5, wherein the electrolytic solution contains at least one type of hexavalent chromium ion selected from the group consisting of chromate ions, dichromate ions, and trichromate ions, the ions being derived from chromium trioxide.

9. 6. The plating apparatus according to claim 5, wherein the content of chromium trioxide in the electrolytic solution is 200 g / L to 300 g / L, and the content of sulfuric acid in the electrolytic solution is 2.0 g / L to 3.0 g / L.

Citation Information

Patent Citations

  • Method for electrodepositing chromium

    JP1986079796A

  • Anode for chromium plating, and its manufacturing method

    JP2001158999A

  • Method for producing peroxodisulfate

    JP2004099914A

  • Method of manufacturing headrest stay

    JP2006304869A

  • Structured chromium solid particle layer and method for producing the same

    JP2011516726A